Factors influencing the adoption of information technology in independent casual dining restaurants - Salleh, Salmalina; Zulkifly, Muhammad Izzat; Ramli, Noorazlin (2010)
The purpose of the paper is to examine factors influencing the adoption of information technology (IT) in independent casual dining restaurants. Sample populations of this study were taken among the manager or owner of the independent casual dining restaurants around Klang Valley which already implemented the IT. Self-administered questionnaires which consist of five sections were used. The overall findings from this study involving 53 managers could be streamlined and at the end it clearly indicates that most of the managers were influenced by motivational factors in decisions making of implementing IT in the restaurants. Thus this study could illustrate a visual to the foodservice operators, body of knowledge and to the government on the restaurant IT adoption scenario in Malaysia. Generally, some useful insights were attained.